Attitude and Academic Performance in English of First Year BEED and BECED Students of Essu-Maydolong - Glino Azura, Zyra Grace; Boco, Rhea Angelica F.; Conopio, Jeffrey B.; Conopio, Marilyn R.; Madriaga, Estelita A. (TWIST, 2024)
The study determined the significant relationship between the attitude and academic performance in English of first year BEED and BECED students of ESSU-Maydolong. The study involves 86 first year BEED and BECED students of ESSU-Maydolong enrolled during the first semester of school year 2022-2023 as a respondents of the study. The study utilized the descriptive correlation method in order to provide the accurate answers to the research problems. The data gathered by the researchers was summarized in a form of frequency distribution and percentages. The researchers analyzed and correlated the variables using Pearson r correlation coefficient. Findings revealed that attitude towards in English of the first year BEED and BECED students of ESSU-Maydolong was “positive” and the academic performance in English was classified as “good”. Result of the study showed that computed r-value of 0.30 is greater than the tabular r-value 0.211 so the researchers rejected the null hypothesis. This implies that the attitude and the academic performance in English of first year BEED and BECED students of ESSU-Maydolong have a significant relationship.